1989
DOI: 10.1177/104063878900100304
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biochemical and Hematologic Values of Normal and Mycobacterium Bovis-Infected American Bison

Abstract: Abstract. Hematologic and serum biochemical tests were used to monitor the health of 3 groups of bison in an experimental study of tuberculosis. Bison were randomly assigned to Mycobacterium bovis-infected, M. bovis -sensitized, and uninfected control groups. Hematologic measurements included total and differential leukocyte counts, hemoglobin (Hb), packed cell volume (PCV), fibrinogen, and plasma proteins. Biochemical tests included serum urea nitrogen, creatinine, aspartate amino transferase, sorbitol dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
1
14
1
Order By: Relevance
“…Perhaps the immune cell populations that are traditionally stimulated by ConA, PWM, and PHAP in cattle are different in bison, leading to a different paradigm of immune response between the two species of ruminants. There is no published record of measurements of immune cell phenotype and specific function of T cell populations (CD4ϩ, CD8ϩ, natural killer cells, ␥␦ T cells) during disease states in bison that would help explain these data; however one study suggested that hematologic parameters are similar between bison and cattle (Miller et al, 1989). It is clear that PWM, a T-cell-dependent B-cell mitogen, was capable of inducing IFN-␥ production by PBMC from bison calves.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the immune cell populations that are traditionally stimulated by ConA, PWM, and PHAP in cattle are different in bison, leading to a different paradigm of immune response between the two species of ruminants. There is no published record of measurements of immune cell phenotype and specific function of T cell populations (CD4ϩ, CD8ϩ, natural killer cells, ␥␦ T cells) during disease states in bison that would help explain these data; however one study suggested that hematologic parameters are similar between bison and cattle (Miller et al, 1989). It is clear that PWM, a T-cell-dependent B-cell mitogen, was capable of inducing IFN-␥ production by PBMC from bison calves.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, free ranging and captive animals often have dramatically different diets, which can be reflected in serum levels of essential minerals such as calcium and phosphorus [1819]. Disease is more intensively controlled in captive animals than in free-living populations, and differences in disease management strategies could contribute to altered biochemical parameters [20]. As such, it is crucial to consider the complex influences of environment factors on the physiological status of wildlife when interpreting biochemical parameters for wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…As to free living wild animal, bovine tuberculosis has been reported in Buffaloes, deer, oryxes, bison antelopes, ferrets. Monkeys and wild rodents such as rats and hares in many area of the world (90,110,144,171,199). Recently an outbreak of tuberculosis was diagnosed in badgers in Great Britain (145).…”
Section: True and Alternate Hostsmentioning
confidence: 99%
“…Because tuberculosis usually assumes a chronic course, evidence of disease is always lacking until the terminal stages when many organs are involved (110,199). The principal sign of tuberculosis is a chronic wasting or emaciation that develops despite good nutrition (144). Most tuberculosis in cattle affects the lungs and adjacent parts of the respiratory tract as the result of inhalation of tubercle bacilli (34,224).…”
Section: Symptomatologymentioning
confidence: 99%
See 1 more Smart Citation